P128 An add-on training program involving breathing exercises, cold exposure, and meditation attenuates inflammation and disease activity in axial spondyloarthritis – a proof of concept trial. (March 2019) - De Jong, H; Buijze, G; Kox, M; van de Sande, M; van Schaardenburg, DJ; van Vugt, R; Popa, C; Picckers, P; Baeten, D
Abstract : Career situation of first and presenting author: Student for a master or a PhD. Introduction: Previous research in healthy individuals showed that the innate immune response can be voluntarily modulated by a training program involving breathing exercises, exposure to cold and meditation 1 . It is unknown whether the same intervention could potentially lead to suppression of inflammation and whether it can safely be applied in patients with chronic inflammatory diseases. Objectives: The objective of this study was to assess safety and anti-inflammatory effects of an add-on training program comprising breathing exercises, cold exposure and meditation in patients with axial spondyloarthritis. Methods: This was an open-label randomised one-way crossover proof-of-concept trial. Participants were randomised to either the early or late intervention group. The intervention consisted of an 8 weeks training program comprising cold exposure, meditation and breathing exercises. Results: There was no significant difference in adverse events between groups, with one serious adverse event occurring 8 weeks after end of the intervention and judged 'unrelated'. After 8 weeks there was a significant decline of the hs-CRP in the intervention group (median [interquartile range] from 10.2 [6.5–17.1] to 6.0 [3.9–15.6] mg/L; p=0.02), but not in the control group (from 8.7 [5.2–17.2] to 13.2 [7.9–20.1] mg/L; p=0.70). A similar trend was seen for serum calprotectin (p=0.07 in intervention versus p=0.31 in control), but not for ESR. In addition, ASDAS-CRP (p=0.02), BASDAI (p=0.04), SF-36 physical component score (p=0.01), EQ-5D (p=0.049), and EQ-5D VAS (p=0.02) decreased significantly in the intervention group, but not the control group. Conclusions: In the present trial we show that the add-on training program involving breathing exercises, cold exposure, and meditation can safely be applied in patients with axial spondyloarthritis, a prototype chronic inflammatory disease. Furthermore, it attenuated inflammation and improved disease activity, function, and quality of life. Reference: Kox M, van Eijk LT, Zwaag J, van den Wildenberg J, Sweep FC, van der Hoeven JG, Pickkers P. Voluntary activation of the sympathetic nervous system and attenuation of the innate immune response in humans. Proc Natl Acad Sci USA 2014 May 20;111(20):7379–84. Acknowledgements: Professor Piet van Riel, Lisa van Maanen, Sanne Pons, Wim Hof, Isa Hof, Henk van den Berg, Marianne Peper, Linda Hochstenbach, and Iris Premssler. Disclosure of Interest: None declared.